Parental indulgence, self-regulation, and young adults' behavioral and emotional problems. Issue 3 (3rd July 2019) - Cui, Ming; Graber, Julia A.; Metz, Allison; Darling, Carol A.
ABSTRACT: Because emotional and behavioral problems during young adulthood are an evolving public health concern, it is important to identify parenting behavior in the family of origin that prevents or exacerbates such problems. Therefore, we tested the impact of a unique parenting behavior – indulgent parenting – on emotional and behavioral problems through effects on self-regulation skills among college students, who face increasing developmental demands and challenges independent of parents. Using a sample of 459 college students, results from structural equation modeling suggested that (1) parental indulgence was positively associated with college students' emotional and behavioral problems and (2) self-regulation mediated the association between parental indulgence and emotional and behavioral outcomes. Further, the findings revealed some perceived gender differences. Implications for parenting and young adult health interventions were discussed.